New insights in Al‐doping effects on the LiNiO2 positive electrode material by a sol‐gel method. (12th February 2021) - Kong, Xiangze; Li, Donglin; Fedorovskaya, Ekaterina O.; Kallio, Tanja; Ren, Xuqiang
Summary: The LiNiO2 (LNO) positive electrode material is one of the most promising high‐voltage alternatives for the layered oxide materials such as LiCoO2 (LCO). However, the poor cyclability still limits widespread commercialization of LNO, whereas crack formation is one of the main issues leading to its premature aging. In this study, a series of Al‐doped LNO (LiNi1−x Alx O2, x = 0, 0.02, 0.04, 0.06) positive electrode materials are synthetized via a simple sol‐gel method. Overall, this study aims at providing new insights of the sol‐gel method and Al‐doped strategy for LNO positive electrode materials. The synthesis is found to readily yield in small nanosized crystals, which alleviate the cracking issue. Besides, the optimized Al‐doping amount (2 at%) in LNO decreases cation mixing and primary particle size resulting in improved layered structure stability attributed to more reversible H2‐H3 phase transitions. As a result, the assembled lithium ion batteries equipped with LiNi0.98 Al0.02 O2 can smoothly run for 400 cycles with a relatively high capacity retention of 81% at 100 mA g − 1 charging‐discharging and a wide operating voltage window of 2.5‐4.5 V. Abstract : Al‐doped LiNiO2 synthesized by the sol‐gel method are studied. Sol‐gel method is found to readily yield in small nanosized crystals, which alleviate the cracking issue of the solid‐state method. 2 at% is the best doping concentration, which can suppress Li + /Ni 2+ cations mixing, improve structure stability and phase transition reversibility in LiNiO2 . This work aims at providing insights that help in optimizing the synthesis of high performance LiNiO2 by Al‐doping strategy via the sol‐gel method.